KEPUTUSAN PEMBELIAN ONLINE MELALUI APLIKASI SHOPEE DI SURAKARTA DITINJAU DARI KUALITAS LAYANAN, ONLINE CUSTOMER REVIEW DAN KEPERCAYAAN - Yoga Endhi Pratama; Sudarwati Sudarwati; Istiqomah Istiqomah (JURNAL ILMIAH EDUNOMIKA, 2019)
Developments in the digital media era as of today, having an online business is indeed one of the most profitable things. Once the community recognizes the online transaction system, it is also known that the user rates of online buying and selling services are increasing. It's what makes online business segments drastically rising. Especially, nowadays more and more selling sites or online marketplace that special provide online buy and sell transactions such as Shopee. Study reserch uses a descriptive and causal approach with a quantitative approach. Questionnaires were used to obtain data from citizens living in all areas of Surakarta. Samples in this study uses of 100 respondents, the research was carried out throughout Surakarta and the time needed in this study was more or less for 3 months. The results of this study indicate that quality of service, online customer review variables and trust have a significant positive effect on online purchasing decision. Keyword: Quality of service, Customer review, Trust, Shopee